2023
DOI: 10.15252/embj.2022113012
|View full text |Cite
|
Sign up to set email alerts
|

TECPR1 conjugates LC3 to damaged endomembranes upon detection of sphingomyelin exposure

Abstract: Invasive bacteria enter the cytosol of host cells through initial uptake into bacteria-containing vacuoles (BCVs) and subsequent rupture of the BCV membrane, thereby exposing to the cytosol intraluminal, otherwise shielded danger signals such as glycans and sphingomyelin. The detection of glycans by galectin-8 triggers anti-bacterial autophagy, but how cells sense and respond to cytosolically exposed sphingomyelin remains unknown. Here, we identify TECPR1 (tectonin beta-propeller repeat containing 1) as a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Ca 2+ leakage will induce the scrambling of sphingomyelin (SM) from the luminal to cytoplasmic membrane surface of the lysosomal membrane (24). SM will subsequently recruit the TECPR1-ATG5-ATG12 E3-like ligase to the damaged membrane (21)(22)(23). Here we show that ATG8 E3-like ligase translocation is an essential prerequisite to ESCRT recruitment, thereby placing the ATG8 E3-like ligases in the role of damage sensors for the ESCRT-mediated membrane repair pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ leakage will induce the scrambling of sphingomyelin (SM) from the luminal to cytoplasmic membrane surface of the lysosomal membrane (24). SM will subsequently recruit the TECPR1-ATG5-ATG12 E3-like ligase to the damaged membrane (21)(22)(23). Here we show that ATG8 E3-like ligase translocation is an essential prerequisite to ESCRT recruitment, thereby placing the ATG8 E3-like ligases in the role of damage sensors for the ESCRT-mediated membrane repair pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We and others recently identified a TECPR1-dependent autophagy E3-like ligase complex which functions independently of ATG16L1 to regulate unconventional ATG8 lipidation at damaged lysosomal membranes (21)(22)(23). Double knockout of both ATG16L1 and TECPR1 was shown to compromise the repair of damaged membranes, suggesting a functionally redundant role for both E3-like ligase complexes in the repair process (21).…”
Section: Escrt Recruitment To Damaged Lysosomesmentioning
confidence: 99%
“…Thus, we can conclude that the Nterminal dysferlin domain of TECPR1 is essential for its lysosomal recruitment in response to damage. In a companion manuscript, Boyle et al (2023) observed TECPR1 recruitment to damaged phagosomal membranes in response to bacterial infection. This recruitment is mediated by a sphingomyelin binding domain identified in the N-terminal dysferlin domain of TECPR1.…”
Section: Tecpr1 Lysosomal Recruitment Is Dependent On Its N-terminal ...mentioning
confidence: 94%
“…Lysosomal damage was recently shown to induce a rapid sphingomyelin translocation from the luminal to cytoplasmic membrane surface (Niekamp et al, 2022), suggesting sphingomyelin enrichment at damaged membranes could represent a conserved TECPR1 recruitment mechanism. To confirm, we introduced a point mutation at W154 of TECPR1, shown by Boyle et al (2023) to be essential for sphingomyelin binding. This single point mutation was sufficient to block TECPR1 lysosomal enrichment in response to LLOMe treatment (Fig EV1A -C).…”
Section: Tecpr1 Lysosomal Recruitment Is Dependent On Its N-terminal ...mentioning
confidence: 99%
“…Chen et al, 2024; Radulovic et al, 2018; Skowyra et al, 2018). Severely damaged lysosomes can be removed by selective autophagy(Chauhan et al, 2016; Maejima et al, 2013), noncanonical autophagy(Boyle et al, 2023; Kaur et al, 2023), or lysosomal exocytosis(Wang et al, 2023). Master regulators mTORC1 (mechanistic target of rapamycin complex 1) and AMPK (AMP-activated protein kinase), located on lysosomes(Sancak et al, 2010; C.-S. Zhang et al, 2014), are finely tuned to respond to lysosomal damage, subsequently activating downstream processes e.g., autophagy and lysosomal biogenesis(Jia et al, 2018; Jia et al, 2020a, b; Jia et al, 2020c).…”
Section: Introductionmentioning
confidence: 99%